2019
DOI: 10.1111/geb.12974
|View full text |Cite
|
Sign up to set email alerts
|

Comparing temperature data sources for use in species distribution models: From in‐situ logging to remote sensing

Abstract: Aim Although species distribution models (SDMs) traditionally link species occurrences to free‐air temperature data at coarse spatio‐temporal resolution, the distribution of organisms might instead be driven by temperatures more proximal to their habitats. Several solutions are currently available, such as downscaled or interpolated coarse‐grained free‐air temperatures, satellite‐measured land surface temperatures (LST) or in‐situ‐measured soil temperatures. A comprehensive comparison of temperature data sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(139 citation statements)
references
References 87 publications
(169 reference statements)
6
131
1
1
Order By: Relevance
“…Climate variables derived using coarse‐resolution data may thus bear little resemblance to conditions experienced by organisms, which at worst may yield highly erroneous predictions, and at best will greatly increase uncertainty (e.g. Lembrechts, Lenoir, et al, ; Suggitt et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Climate variables derived using coarse‐resolution data may thus bear little resemblance to conditions experienced by organisms, which at worst may yield highly erroneous predictions, and at best will greatly increase uncertainty (e.g. Lembrechts, Lenoir, et al, ; Suggitt et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This mismatch greatly hinders scientific understanding of the mechanisms explaining how organisms interact with their environment (Kearney & Porter, ) and hampers efforts to address the applied challenges such as predicting the ecological consequences of climate change (Potter et al, ; Suggitt et al, ). Spatial variability in microclimate greatly exceeds the magnitude of climate change expected in the upcoming century, and ignoring this variability leads to erroneous predictions of climate change impacts on species distributions (Gillingham, Huntley, Kunin, & Thomas, ; Lembrechts, Lenoir, et al, ; Lenoir, Hattab, & Pierre, ), population dynamics (Bennie et al, ) and behaviour (Blackshaw & Blackshaw, ). Failing to account for temporal variability also hinders quantification of exposure to extreme conditions (Parmesan, Root, & Willig, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In large part, these disparities can be attributed to the fact that coarse-gridded temperature surfaces, such as WorldClim2, are interpolated from weather stations that are located in open habitats (De Frenne et al, 2019;Frenne and Verheyen, 2016). Several recent studies have reported similarly striking differences (Jucker et al, 2018;Lembrechts et al, 2019;Potter et al, 2013;Storlie et al, 2014). Near-surface temperatures can only be accurately measured with in-situ loggers or with emerging remote sensing technologies, such as airborne laser scanning (Jucker et al, 2018).…”
Section: Journal Of Experimental Biology • Accepted Manuscriptmentioning
confidence: 99%
“…It is also microclimatic temperatures that individual organisms experience on a day-to-day basis and which can affect the distribution and abundance of species at the local scale. Therefore, information on how individuals respond to finescale microclimatic temperature variation over short time-periods (Bladon et al, 2019;Ide, 2002;Kelly, Godley, & Furness, 2004) may need to be incorporated into models to accurately predict species' responses to climate change (Kearney, Shine, & Porter, 2009;Lembrechts et al, 2019). For example, it is likely that a diversity of K E Y W O R D S behavioural thermoregulation, butterflies, climate change, generalist, microclimate, population trends, specialist, temperature microclimates at the local scale could protect species from wider temperature change, by providing pockets of favourable microclimate for temperature-sensitive species (Thomas & Simcox, 2005).…”
Section: Introductionmentioning
confidence: 99%